The exhibition spaces and their contradictions: possibilities of dialogue with schools (Palíndromo, 2025)
The relationship between art museums and public schools is permeated by historical challenges: On the one hand, museums have assumed a pedagogical function since their modern origins, but they have historically acted as instruments of legitimization of an elitist and hegemonic cultural vision. On the other hand, public schools face structural limitations in ensuring systematic access to artistic productions. This article aims to problematize how the connection between art teachers and exhibition spaces can broaden students' aesthetic repertoire, taking as reference data from the Research Project Contemporary Art Exhibition Spaces, Dialogues with Virtual Training Environments, and the Teacher Training Observatory in the Scope of Art Education, both linked to the Center for Arts, Fashion, and Design at UDESC. The research, grounded in historical-dialectical materialism, combined a bibliographic review, documentary analysis, and project data, articulating: a) considerations regarding the role of art museums as didactic spaces, with an emphasis on disputes during the Cold War and the role of MASP; b) the limits and challenges faced by art teachers in the face of the precariousness of teaching work and unequal access to cultural spaces; c) the results of the training course in contemporary art offered within the scope of the project, which aimed to broaden the critical and aesthetic repertoire of basic education teachers. It is concluded that the rapprochement between schools and museums depends on effective public policies, infrastructure, continuing education and the recognition of art as a formative right.
Keywords: art education; exhibition spaces; contemporary art; teacher training